Care protocol in third molar surgery in diabetic patients: a bibliographic review - Cantos-Álvarez, Belén (2022)
Diabetes is a metabolic disorder, caused by an increase in blood glucose, which commonly affects a large population worldwide. That is why diabetic patients in certain cases require dental care, due to their high prevalence of oral problems or the need for third molar extraction. Due to the above, a bibliographic review was carried out in the Scielo, Pubmed, and Google Scholar databases. There were no language restrictions and 130 articles were considered, according to the inclusion and exclusion criteria, 50 articles with a maximum age of 5 years were selected. As a result, it was possible to establish a care protocol for third molar surgery in diabetic patients, taking into account the different parameters that must be carried out before the surgical procedure. It is concluded that a care protocol in third molar surgery must contemplate a successful treatment plan, taking into account the most significant steps such as filling out the clinical history and preoperative glycemic control.